2013
DOI: 10.1590/s0102-67202013000200009
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da frequência em consultas nutricionais dos pacientes após cirurgia bariátrica

Abstract: There was a high dropout of the patients in post-operative nutritional attendance, being primarily concerned about the high dropout after two years of surgery; this tendency may result in metabolic complications and regain of lost weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 17 publications
0
4
0
11
Order By: Relevance
“…In Brazil, despite extensive research, we found no specific studies on the rates of medical-surgical followup, only nutritional. The rates presented for adherence to nutritional follow-up varied significantly between one year (51% and 56%), two years (25.37%) and over two years (14.93%) post-surgery 12,20,21 . These results call attention to the possibility of patients recovering their old habits, mainly with problems associated with weight.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, despite extensive research, we found no specific studies on the rates of medical-surgical followup, only nutritional. The rates presented for adherence to nutritional follow-up varied significantly between one year (51% and 56%), two years (25.37%) and over two years (14.93%) post-surgery 12,20,21 . These results call attention to the possibility of patients recovering their old habits, mainly with problems associated with weight.…”
Section: Resultsmentioning
confidence: 99%
“…Studies point to the predominance of women. Study analyzed 469 monitoring reports of which 83% were women and 16.8% men 13 . It is known that the woman weight control has strong aesthetic motivation and presents important emotional components in relation to food.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the improvement in the postoperative food pattern in relation to the preoperative period, when analyzing the evolution of the diet during the three, six and 12 postoperative months, it was observed that the adequate consumption of foods that contribute to glycemic control is more prevalent up to six months postoperatively. This fact suggests a higher concern of patients in the immediate postoperative period, when the diet has specific characteristics, reflecting the lack of understanding of the importance of food re-education in long-term surgical success 13 .…”
Section: Discussionmentioning
confidence: 99%